Analisis Pengaruh Pertumbuhan Penduduk Terhadap Pertumbuhan Ekonomi Di Kabupaten Agam Tahun 2010 - 2021 - Fitri Wulandari; Elvi Zuriyani; Nila Afryansih (FKIP, Universitas Palangka Raya, 2023)
This study aims to obtain data, process, and analyze the results of increasing the number of people with economic progress in Agam Regency in 2010 - 2020 can be seen from: 1) population growth in Agam Regency in 2010 - 2020. 2) Agam economic development in 2010 - 2020 3) the effect of population growth on economic progress in Agam Regency in 2010-2020. The type of research used in this research is descriptive quantitative research which is a quantitative research in the form of a description with numbers or numeric. The sample in this study is total sampling where all data are taken from population growth and economic growth in Agam district. The results obtained from this study: 1) from the last 10 years there has been a fluctuation in the population growth of Agam Regency. 2) Agam Regency's economic growth has increased and decreased where the highest economic growth was in 2012 as much as 6.18% and the lowest was in 2020 with a figure of -1.38%. 3) the increase in population has a significant positive impact on economic growth in Agam Regency.